Masculinity Beyond the Metropolis - Kenway, J. author. aut Link
IX, 230 p.
Keywords: This book gives insights on youth, masculinity and place by exploring spatially marginalized masculinities in stigmatized and romanticized out-of-the-way places in 'developed' Western countries. It shows the impact of globalization on place and identity through global ethnographic studies and media representations of young men in peripheral places.